Arsenic(V) removal from enargite leach solutions by precipitation of magnesium ammonium arsenate. Issue 11 (24th July 2019) - Li, Tengfei; Zhang, Yansheng; Zhang, Bo; Chang, Kexin; Jiao, Fen; Qin, Wenqing
ABSTRACT: This study investigated a potential method for the removal of arsenic from enargite leach solution containing 5.86 g/L As(V) by precipitation of magnesium ammonium arsenate (MAA). The experimental results showed the As(V) concentration can be reduced to 1.8 mg/L under the optimum conditions. The molar ratio NH4 /Mg/As in precipitates formed at different pH values was checked by wet chemical analysis, indicating that some of by-products such as Mg3 (AsO4 )2, Mg(OH)2, and MgHAsO4 will be formed at the solution pH above or below pH 9.5. Notably, this study indicated MAA has a better ability for arsenic removal than magnesium arsenate. The precipitates also were characterized by XRD and SEM.